The Implementation of The Village SDGS Program: Factors and Importance Performance Analysis - Yefni Yefni; Rosmita Rosmita; Rina Silvya Lubis; Y Rahmat Akbar; Abather Saadoon (Jurnal Mamangan, 2024)
The implementation of the Village SDGs program is expected to improve the welfare of village communities. However, the large number of SDGs indicators means that the implementation of this program is not focused and does not get optimal results. This research aims to find out what factors in the Village SDGs program are important issues for the people of the Kepulauan Meranti district and how the performance of the Village SDGs program compares with the expectations of the people of the Kepulauan Meranti District. The theory used is the Theory of Sustainable Development by Jeffrey Sachs in 2015. The method used is cross-sectional quantitative analysis with factor analysis and importance performance analysis techniques. The respondents in this research were the people of Meranti Islands Regency, Riau Province, totaling 382 participants from each sub-district. The research results show that all variables in the Village SDGs program are priority factors and important problems for the people of Meranti Islands Regency, especially the SDGs (X1) program, namely the problem of poverty alleviation. The results of the important performance analysis show that the variables in quadrant I are X1, X6, X9, X12 and the variables in quadrant II are X2, X4, X5, X16. The variables in quadrant III are X8, X10, X11, X13, X15 and the variables in quadrant IV are X3, X7, X14, X17, X18. The novelty in this research is the implementation of the village SDGs program from the local community's perspective.